Meta-analyses including non-randomized studies of therapeutic interventions: a methodological review. Issue 1 (December 2016) - Faber, Timor; Ravaud, Philippe; Riveros, Carolina; Perrodeau, Elodie; Dechartres, Agnes
Abstract Background There is an increasing number of meta-analyses including data from non-randomized studies for therapeutic evaluation. We aimed to systematically assess the methods used in meta-analyses including non-randomized studies evaluating therapeutic interventions. Methods For this methodological review, we searched MEDLINE via PubMed, from January 1, 2013 to December 31, 2013 for meta-analyses including at least one non-randomized study evaluating therapeutic interventions. Etiological assessments and meta-analyses with no comparison group were excluded. Two reviewers independently assessed the general characteristics and key methodological components of the systematic review process and meta-analysis methods. Results One hundred eighty eight meta-analyses were selected: 119 included both randomized controlled trials (RCTs) and non-randomized studies of interventions (NRSI) and 69 only NRSI. Half of the meta-analyses (n  = 92, 49 %) evaluated non-pharmacological interventions. "Grey literature" was searched for 72 meta-analyses (38 %). An assessment of methodological quality or risk of bias was reported in 135 meta-analyses (72 %) but this assessment considered the risk of confounding bias in only 33 meta-analyses (18 %). In 130 meta-analyses (69 %), the design of each NRSI was not clearly specified. In 131 (70 %), whether crude or adjusted estimates of treatment effect for NRSI were combined was unclear or not reported. Heterogeneity across studies was assessed in 182 meta-analyses (97 %) and further explored in 157 (84 %). Reporting bias was assessed in 127 (68 %). Conclusions Some key methodological components of the systematic review process—search for grey literature, description of the type of NRSI included, assessment of risk of confounding bias and reporting of whether crude or adjusted estimates were combined—are not adequately carried out or reported in meta-analyses including NRSI.